The Effectiveness of Using Picture-Based Flip Books in Mastery of Maharah Qiraah for Grade IV Students in MIMA 01 KH Shiddiq Jember - Nisa', Deafitri Arifatun; Maknunah, Durrotul (Yayasan Al-Aziziyah Tlogoagung Kedungadem Bojonegoro, 2024)
This study aims to evaluate the effectiveness of the use of picture-based flip books in mastering maharah qiraah in grade 4 students at MIMA 01 KH Shiddiq Jember. The method used in this study is quantitative research with an experimental type. The research sample consisted of 40 randomly selected students. Data was collected through pre- and post-use tests of flip books, as well as questionnaires to measure students' responses to learning media. Data analysis was carried out using descriptive and inferential statistics. The results showed that there was a significant increase in students' mastery of maharah qiraah after using the flip book, with the average score in the postest higher compared to the pretest test. In addition, students' responses to the use of flip books showed positive results, which indicates that this media is interesting and effective in supporting learning. This study concludes that gamba-based flip books. Educators can improve the teaching of Arabic so that they can improve the quality of learning.